2016
DOI: 10.12659/msm.898420
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gait Symmetry After Training on a Treadmill with Biofeedback in Chronic Stroke Patients: A 6-Month Follow-Up From a Randomized Controlled Trial

Abstract: BackgroundOne of the most significant challenges for patients who survive a stroke is relearning basic motor tasks such as walking. The goal of this study was to evaluate whether training on a treadmill with visual biofeedback improves gait symmetry, as well as spatiotemporal and kinematic gait parameters, in stroke patients.Material/MethodsThirty patients in the chronic phase after a stroke were randomly allocated into groups with a rehabilitation program of treadmill training with or without visual biofeedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 31 publications
(31 reference statements)
0
38
0
1
Order By: Relevance
“…Positive changes in walking biomechanics were noted in both groups. An earlier study by the same authors demonstrated improvement in gait symmetry and spatiotemporal parameters [18]. Other researchers [19] demonstrated a positive response to BFB training using a specific parameter (stance phase).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Positive changes in walking biomechanics were noted in both groups. An earlier study by the same authors demonstrated improvement in gait symmetry and spatiotemporal parameters [18]. Other researchers [19] demonstrated a positive response to BFB training using a specific parameter (stance phase).…”
Section: Introductionmentioning
confidence: 80%
“…In a study carried out by Druzbicki et al [17], no significant effect of BFB training was noted. However, some effect was noted in their earlier study [18]. In the research of Gente et al [12], training was based on the ground reaction force at the end of the stance phase, with both visual and auditory feedback.…”
Section: Introductionmentioning
confidence: 94%
“…Overall lower extremity motor deficit is another patient selection criterion, but the measurement tools and cutoff points used to quantify level of deficit vary widely ( 1 , 8 , 23 ). Past studies have included stroke survivors at a specific Brunnstrom stage of recovery ( 21 , 22 ) or with ability to ambulate a predetermined distance or time ( 1 , 23 , 24 ).…”
Section: Key Methodological Factors Influencing Response To Gait Biofmentioning
confidence: 99%
“…However, most stroke studies consider cognition, level of gross motor deficit, and level of visual deficit when selecting patients. Exclusion criteria for cognitive deficits have the highest degree of uniformity, with several studies setting a mini-mental state exam score cutoff at 24 for inclusion (21)(22)(23).…”
Section: Participant Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation